Low-temperature oxidation catalyst for VOCs (Volatile Organic Compounds) in exhaust gas in automobile repair industry, preparation method and application

By using low-temperature oxidation catalysts of PtO2, CeO2 and TiO2 in the auto repair industry, combined with honeycomb ceramic support and preparation methods, the problem of high usage and high energy consumption of precious metal catalysts in waste gas treatment is solved, and high efficiency and low cost are achieved VOCs removal effect.

CN119158593APending Publication Date: 2024-12-20CHINESE RES ACAD OF ENVIRONMENTAL SCI

Patent Information

Application Number
CN202411300056.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the auto repair industry, the use of precious metal catalysts during the treatment of waste gas VOCs in the process of treatment of waste gas in high volume, high energy consumption and high cost.

Method used

Using a low-temperature oxidation catalyst including PtO2, CeO2 and TiO2, honeycomb ceramics are used as a support, and the preparation method of acidification etching and active component coating is reduced to the amount of precious metals and catalytic activity is improved.

Benefits of technology

The mixed gases such as benzene, acetone, dichloroethane, etc. are effectively removed below 320°C, and the conversion rate can reach more than 99%, reducing energy consumption and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158593A_ABST
    Figure CN119158593A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature oxidation catalyst for VOCs (volatile organic compounds) in exhaust gas in the automobile repair industry, a preparation method and application. The catalyst comprises the following active components: PtO2, CeO2 and TiO2. The carrier of the catalyst comprises the following components: SiO2, Al2O3, MgO, Fe2O3, CO2 and ZrO2. According to the low-temperature oxidizing agent, the honeycomb ceramic serves as a carrier, PtO2 serves as a catalyst active component, and a CeO2 rare earth material is used in the active component, so that the dosage of precious metal is reduced, and the catalytic activity of the catalyst can be remarkably improved; meanwhile, a TiO2 component is added into the catalyst, so that the oxidation reaction temperature of the VOCs is reduced; according to the preparation method of the catalyst, the use amount of the noble metal is small, the prepared catalyst is low in cost, and the conversion rate of treating mixed gas of benzene series, acetone and dichloroethane at the temperature of 320 DEG C or below can reach 99% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental pollution control, and in particular to a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, a preparation method and an application thereof. Background Art

[0002] The main pollutant emission link in the auto repair industry is the spraying of auto parts. After being polished and cleaned, the auto parts enter the spray paint room. A large amount of organic waste gas is generated during the spray paint process. The waste gas contains a certain concentration of volatile organic compounds (VOCs). The main components of VOCs pollutants in auto repair waste gas are as follows:

[0003]

[0004] As can be seen from the table above, the main components of the exhaust gas are benzene series, mainly toluene, xylene and trimethylbenzene, with the highest concentration reaching 115 mg / m 3 , is an important active component of ozone precursors and can cause serious environmental pollution.

[0005] The catalytic oxidation method can remove VOCs efficiently. Its core lies in the fact that the catalyst reduces the combustion temperature and improves the oxidation efficiency. The currently commonly used VOCs catalyst honeycomb ceramic-based precious metal catalyst uses honeycomb ceramics as catalyst carriers. One or more of the precious metals Pt, Pd, and Ru are dispersed inside the honeycomb ceramic or attached to the surface of the honeycomb ceramic. The porous honeycomb increases the contact probability between the active components of the catalyst and the exhaust gas. However, when using precious metal catalysts for catalytic oxidation and degradation of VOCs, there are disadvantages such as high cost, poor thermal stability, and easy carbon and chlorine accumulation leading to catalyst deactivation, which is not conducive to large-scale application. Summary of the invention

[0006] In view of this, the present invention provides a low-temperature oxidation catalyst, preparation method and application of VOCs in exhaust gas from the auto repair industry to solve the technical problems of large dosage, high energy consumption and high cost in the process of using conventional precious metal catalysts to treat large-volume and low-concentration exhaust gas in the auto repair industry.

[0007] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.

[0008] The present invention adopts the following technical solution:

[0009] The invention provides a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry. The active components of the catalyst include: PtO2, CeO2 and TiO2.

[0010] Furthermore, among the active components of the catalyst, the weight percentage of PtO2 in the catalyst is 150-500 mg / kg, the weight percentage of CeO2 in the catalyst is 2.0-3.5w%, and the weight percentage of TiO2 in the catalyst is 1.0-1.8w%.

[0011] Furthermore, the catalyst carrier is honeycomb ceramic.

[0012] Furthermore, the carrier components of the catalyst include: SiO2, Al2O3, MgO, Fe2O3, CO2 and ZrO2.

[0013] Furthermore, in the catalyst, the weight proportion of the carrier is 94-98%.

[0014] Furthermore, in terms of weight percentage, the carrier components of the catalyst include: 38-48w% SiO2, 35-45w% Al2O3, 8-12w% MgO, 0.1-0.5w% Fe2O3, 0.1-0.5w% CO2 and 0.2-0.7w% ZrO2.

[0015] The present invention provides a method for preparing a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, comprising:

[0016] Obtain ceramic raw materials and prepare a carrier of the catalyst, wherein the carrier of the catalyst is a honeycomb ceramic; wherein, by mass percentage, the ceramic raw materials contain 38-48% SiO2, 35-45% Al2O3, 8-12% MgO, 0.1-0.5% Fe2O3, 0.1-0.5% CO2, 0.2-0.7% ZrO2, and less than 2% H2O;

[0017] The honeycomb ceramic is immersed in a HNO3 solution with a pH value of 4-6 for acid etching, filtered out and neutralized with a NaOH solution with a pH value of 8-9, and rinsed with deionized water for 3-5 times. After drying, the active component is coated to obtain a finished catalyst.

[0018] Furthermore, the process of coating the active component includes:

[0019] S1: weigh the honeycomb ceramic;

[0020] S2: Weigh a certain amount of Ce(NO3)3·6H2O, Pt(NO3)2 and TiF4 powders, place them in deionized water, and stir them with a magnetic stirrer for 0.5 h until they are fully dissolved;

[0021] S3: placing the honeycomb ceramic in the mixed solution, slowly adding 5w% NH3·H2O solution until the pH is 10, and then sealing and aging at room temperature for 12 hours;

[0022] S4: Wash the sample alternately with anhydrous ethanol and deionized water 3 times each;

[0023] S5: Dry the washed sample in an oven at 90°C for 12 h;

[0024] S6: The obtained precursor was calcined in a muffle furnace at 500 °C for 3 h, with the heating rate set at 2 °C min -1 ;

[0025] S7: Allow the finished catalyst calcined in the muffle furnace to cool naturally to room temperature.

[0026] The present invention provides an application of a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, which is used for removing VOCs in exhaust gas from spray paint booths.

[0027] The beneficial effects brought by the present invention are as follows: the low-temperature oxidant of the present invention uses honeycomb ceramics as a carrier, adopts PtO2 as a catalyst active component, and uses CeO2 rare earth material in the active component, which not only reduces the amount of precious metals used, but also can significantly improve the catalytic activity of the catalyst; at the same time, TiO2 components are added to the catalyst to reduce the oxidation reaction temperature of VOCs; the catalyst preparation method of the present invention uses a small amount of precious metals, the prepared catalyst has a low cost, and the conversion rate of the mixed gas of benzene, acetone and dichloroethane below 320°C can reach more than 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is a schematic diagram of the simulated treatment effect of the catalyst provided by the present invention on auto repair exhaust gas;

[0030] Figure 2 This is a scanning electron microscope image of the Pt424 catalyst;

[0031] Figure 3 This is the XPS graph of Pt424 catalyst. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention provides a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, which can effectively solve the problem of low low-temperature oxidation efficiency and significantly reduce the amount of precious metal PtO2 used.

[0034] The catalyst includes two types: carrier and active component; the carrier is a substance used to disperse and support the active component in the catalyst, which provides a larger surface area so that the active component can contact the reactant more effectively; the active component is the part of the catalyst that actually participates in the chemical reaction and is the key component for the catalyst to work.

[0035] The active components of the catalyst include: PtO2, CeO2 and TiO2.

[0036] Among the active components of the catalyst, the weight percentage of PtO2 in the catalyst is 150-500 mg / kg, the weight percentage of CeO2 in the catalyst is 2.0-3.5w%, and the weight percentage of TiO2 in the catalyst is 1.0-1.8w%. The molar ratio of CeO2 to TiO2 is about 1:1.

[0037] The catalyst carrier is honeycomb ceramic.

[0038] The carrier components of the catalyst include: SiO2, Al2O3, MgO, Fe2O3, CO2 and ZrO2. Among them, the main components of the carrier of the catalyst are SiO2 and Al2O3, and the content of the two accounts for 73-93% of the total amount of the catalyst. The remaining components are MgO, Fe2O3 and CO2. In order to improve the strength and corrosion resistance of the carrier, it is necessary to introduce about 0.2-0.7% of zirconium silicate into the raw material, and these components account for about 8-14% of the total amount of the catalyst.

[0039] In the catalyst, the weight proportion of the carrier is 94-98%.

[0040] Measured by weight percentage, the carrier components of the catalyst include: 38-48w% SiO2, 35-45w% Al2O3, 8-12w% MgO, 0.1-0.5w% Fe2O3, 0.1-0.5w% CO2 and 0.2-0.7w% ZrO2.

[0041] For example, the catalyst carrier components include, by weight percentage, 38w% SiO2, 35w% Al2O3, 8w% MgO, 0.1w% Fe2O3, 0.1w% CO2 and 0.2w% ZrO2. Of course, the remaining components may be inevitable impurities.

[0042] The present invention adopts PtO2 as the active component of the catalyst. PtO2 is a highly efficient catalyst that can promote chemical reactions, especially in oxidation reactions. It is used as the main active component of the low-temperature oxidation catalyst for VOCs in exhaust gas in the auto repair industry to accelerate the oxidation process of VOCs.

[0043] In order to reduce the amount of precious metals, CeO2 rare earth materials are used in the active component. Since Ce-based materials have good oxygen storage and release capabilities, the catalytic activity of the catalyst can be significantly improved. CeO2 has good oxygen storage and release capabilities, which means that it can store oxygen in chemical reactions and release it when needed, helping to maintain the oxygen concentration on the catalyst surface, thereby improving catalytic activity.

[0044] At the same time, in order to reduce the temperature of VOCs oxidation reaction, TiO2 is added to the catalyst. TiO2 is added to the catalyst to reduce the temperature of VOCs oxidation reaction. By adding TiO2, the catalyst can effectively promote the oxidation of VOCs at a lower temperature, which is very important for energy saving and reducing operating costs.

[0045] The present invention can reduce the amount of precious metal Pt by using CeO2 and TiO2, thereby reducing the preparation cost of the catalyst. Since the use of precious metals is reduced, the preparation cost of the overall catalyst is also reduced. Under the temperature condition of below 290°C, the conversion rate of the catalyst for mixed gases such as benzene series, acetone, and dichloroethane is more than 90%, and under the temperature condition of below 320°C, the conversion rate of the mixed gas is more than 99%. This means that it can efficiently treat these harmful gases at a relatively low temperature, improve the treatment efficiency, and reduce energy consumption.

[0046] The design of the catalyst of the present invention utilizes the high catalytic activity of PtO2, and at the same time reduces the amount of precious metals and the processing temperature through the synergistic effect of CeO2 and TiO2, thereby realizing a highly efficient, economical VOCs processing catalyst suitable for low temperature conditions.

[0047] like Figure 1-3 As shown, the implementation effect is:

[0048] Embodiment 1:

[0049] The Pt237 catalyst uses a PtO2 content of 237 mg / kg, and the CeO2 and TiO2 contents are 2.8% and 1.4% respectively. The SiO2, Al2O3, MgO, Fe2O3, and ZrO2 contents in the honeycomb ceramic used by the Pt237 catalyst are 42.5%, 38.1%, 9.3%, 0.2%, and 0.5% respectively.

[0050] Embodiment 2:

[0051] The Pt424 catalyst uses a PtO2 content of 424 mg / kg, and the contents of CeO2 and TiO2 are 2.6% and 1.3% respectively. The contents of SiO2, Al2O3, MgO, Fe2O3, and ZrO2 in the honeycomb ceramic used by the Pt424 catalyst are 42.5%, 38.1%, 9.3%, 0.2%, and 0.5% respectively.

[0052] Blank test:

[0053] The contents of SiO2, Al2O3, MgO, Fe2O3 and ZrO2 in the honeycomb ceramic used in the blank test are 42.5%, 38.1%, 9.3%, 0.2% and 0.5% respectively. The blank test is carried out by using the honeycomb ceramic without adding active components, and the catalyst fired by the present invention is compared, and the active components of the Pt237 catalyst and the Pt424 catalyst are both in the form of coating, that is, the finished catalyst is obtained by coating with active components.

[0054] In the comparative test, the simulated gas was toluene 100 mg / m 3 , ethylbenzene 100mg / m 3 , Xylene 100mg / m 3 , trimethylbenzene 100mg / m 3 , Vinyl chloride 500mg / m 3 , acetone 500mg / m 3 , Ethylene dichloride 500mg / m 3 The rest is air.

[0055] A quartz tube with an inner diameter of 12 mm was used as the fixed reactor bed, the length of the tube furnace was 500 mm, and the catalyst design space velocity was 20,000 h -1 .

[0056] like Figure 1 As shown, Figure 1 It shows that when no active components are introduced, the total hydrocarbon concentration is tested using an FID detector for the above simulated gas, and the conversion rate of the blank test group does not change much with temperature. When the temperature rises from 140°C to 320°C, the conversion rate increases from 4% to about 9%.

[0057] When Pt237 catalyst is used, the conversion rate increases from 10% to about 91% when the temperature rises from 140℃ to 320℃. 90 (Temperature at which the conversion rate reaches 90%) is approximately 310°C.

[0058] When using Pt424 catalyst, the conversion rate increases from 13% to more than 99% when the temperature rises from 140℃ to 320℃. 90 The reaction temperature is 273°C, which significantly reduces the reaction temperature, achieving the effect of energy saving and carbon reduction.

[0059] The present invention also provides a method for preparing a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, comprising the following steps:

[0060] First, ceramic raw materials are obtained to prepare the carrier of the catalyst, and the carrier of the catalyst is honeycomb ceramic. Specifically, the catalyst of the present invention uses honeycomb ceramic as the catalyst carrier, and the honeycomb ceramic raw materials mainly use raw materials such as kaolin, porcelain stone, and feldspar, wherein, by mass percentage, the SiO2 content in the ceramic raw materials is 38-48%, the Al2O3 content is 35-45%, the MgO content is 8-12%, the Fe2O3 content is 0.1-0.5%, the CO2 content is 0.1-0.5%, the ZrO2 content is 0.2-0.7%, and the H2O content is less than 2%.

[0061] SiO2 is one of the main components of ceramic raw materials, which gives the material good chemical stability and mechanical strength. Al2O3 improves the hardness and wear resistance of the material. MgO can improve the sintering performance and thermal stability of ceramics. ZrO2 can improve the thermal stability and toughness of ceramics.

[0062] The content of SiO2 and other components in the catalyst carrier can be controlled by changing the amount of quartz added. Quartz is the main source of SiO2. By adjusting the amount of quartz added to the ceramic raw material mixture, the content of SiO2 in the final catalyst carrier can be accurately controlled. Changes in SiO2 content will affect the physical and chemical properties of the ceramic carrier, such as thermal stability, mechanical strength and catalytic activity.

[0063] The honeycomb ceramic catalyst is fired in one piece at a temperature of 1250-1450°C, which is enough to make the components in the ceramic material react chemically to form a solid ceramic structure. The specifications of the honeycomb ceramic are 100mm×100mm×50mm, the pore size is 1.5mm×1.5mm, and the wall thickness is 0.5mm. The pore size of 1.5mm×1.5mm refers to the size of the internal channel of the ceramic carrier, that is, the width and height of each hole. This pore size can provide an appropriate channel size so that the catalyst and the reactant can fully contact.

[0064] Then, the honeycomb ceramic is immersed in a HNO3 solution with a pH value of 4-6 for acid etching, filtered out and neutralized with a NaOH solution with a pH value of 8-9, and rinsed with deionized water for 3-5 times. After drying, the active component is coated to obtain a finished catalyst.

[0065] The honeycomb ceramic carrier is immersed in a HNO3 solution with a pH of 4-6. The purpose of this step is to etch the ceramic surface through the action of acid, increase its specific surface area and porosity, and thus provide more active sites for the active components to attach. The acidic environment with a pH of 4-6 can effectively remove impurities on the ceramic surface, such as metal oxides, and form a rougher surface, which is conducive to the fixation of active components.

[0066] After acid etching, the honeycomb ceramic needs to be removed from the HNO3 solution. This step is usually achieved by filtering to separate the solid ceramic carrier. The acidified ceramic carrier is neutralized with a NaOH solution with a pH value of 8-9. This step is to neutralize the acid remaining on the ceramic surface to prevent the acid from affecting the active components subsequently coated. The neutralization reaction can eliminate the corrosion under acidic conditions and ensure the stability of the catalyst carrier.

[0067] Rinse the ceramic support 3-5 times with deionized water to thoroughly remove the NaOH and other ions that may remain during the neutralization process to prevent these substances from affecting the coating of the active components and the performance of the catalyst. The washed ceramic support needs to be dried to remove surface moisture. Drying can be done in an oven, air drying or other suitable methods to ensure that the support is completely dry before coating the active components.

[0068] The active components, namely PtO2, CeO2 and TiO2, are coated on the surface of the dried ceramic carrier. This step is to evenly coat the precursor solution of the active components on the carrier surface, and then fix the active components through processes such as drying and calcination. After the above steps, the honeycomb ceramic carrier is evenly coated with active components, forming a finished catalyst with specific catalytic functions.

[0069] Specifically, the process of coating the active component includes:

[0070] S1: Weigh the honeycomb ceramic, that is, weigh one or more complete honeycomb ceramic catalyst carriers.

[0071] S2: Use an electronic balance to weigh a certain amount of Ce(NO3)3·6H2O, Pt(NO3)2 and TiF4 powder respectively, place them in deionized water, and use a magnetic stirrer to stir for 0.5 h until they are fully dissolved.

[0072] Ce(NO3)3·6H2O is used to provide CeO2 active component in the catalyst. Pt(NO3)2 is used to provide PtO2 active component in the catalyst. TiF4 is used to provide TiO2 active component in the catalyst. The purpose of stirring is to ensure that Ce(NO3)3·6H2O, Pt(NO3)2 and TiF4 powders can be completely dissolved in deionized water to form a uniform solution. This is a key step in the subsequent coating process, because only a uniform solution can ensure the uniform distribution of active components on the ceramic carrier.

[0073] S3: Place the honeycomb ceramic in the mixed solution, slowly add 5w% NH3·H2O solution until pH=10, and then seal and let stand for aging at room temperature for 12 hours.

[0074] In order to evenly coat the outer surface of the honeycomb ceramic carrier and the inner surface of the honeycomb pores with active components, the honeycomb ceramic carrier needs to be completely immersed in the mixed solution prepared by S2. The co-precipitation method is adopted, that is, 5% (wt) NH3·H2O solution is added to the mixed solution prepared by S2 in which the honeycomb ceramic carrier is immersed until the pH is 10, in order to convert Ce(NO3)3, Pt(NO3)2 and TiF4 into precipitable metal hydroxides. By sealing and aging at room temperature, the active components of Ce, Pt and Ti can be evenly coated on the honeycomb ceramic carrier, preparing for the subsequent drying and calcining steps.

[0075] S4: Wash the sample alternately with anhydrous ethanol and deionized water for 3 times each.

[0076] After static aging, a uniform active component metal hydroxide coating has formed on the outer surface of the sample and the inner surface of the honeycomb pores. In order to remove other impurities, it is necessary to remove it from the mixed solution and wash it multiple times. The purpose of adding deionized water is to remove soluble impurities, and the purpose of adding anhydrous ethanol is to remove impurities in the micropores on the inner surface of the honeycomb.

[0077] S5: Place the washed sample in an oven at 90°C and dry for 12 hours.

[0078] The washed samples were placed in an oven set at 90°C, which is a relatively high temperature that can quickly remove residual moisture and solvents in the samples without damaging the active components in the samples.

[0079] S6: The obtained precursor was calcined in a muffle furnace at 500 °C for 3 h, with the heating rate set at 2 °C min -1 .

[0080] During the catalyst preparation process, the active components usually exist in the form of precursors, which will be converted into active components during the subsequent calcination process. The temperature is maintained at 500°C in the muffle furnace for 3 hours. This high temperature and time are sufficient to cause chemical reactions in the precursors to occur, thereby forming stable active components.

[0081] S7: Allow the finished catalyst calcined in the muffle furnace to cool naturally to room temperature. Take a catalyst of appropriate length along the honeycomb hole direction according to the designed space velocity for performance evaluation, or directly apply the whole catalyst to the catalytic oxidation reaction.

[0082] The purpose of natural cooling is to avoid additional stress or damage to the catalyst during the cooling process and ensure the structural stability of the catalyst. After cooling to room temperature, the catalyst can be safely removed for subsequent testing, storage or application.

[0083] The present invention also provides an application of a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, which is used for removing VOCs in exhaust gas from spray paint booths.

[0084] The invention adopts PtO2 as the active component of the catalyst, and adds CeO2 rare earth material and TiO2 components to the active component. The preparation method uses a small amount of precious metal, the prepared catalyst has low cost, and the conversion rate of the mixed gas of benzene series, acetone and dichloroethane can reach more than 99% at below 320°C.

[0085] According to the VOCs low-temperature oxidation catalyst prepared by the present invention, the catalyst raw material source is wide, easy to obtain, the structure is strong, can withstand certain pressure and wear, the material is stable, not easy to degrade, can maintain catalytic activity for a long time, and the cost is low. The amount of precious metal used in the active component is small, the raw material is easy to obtain, the cost is low, and the catalyst can effectively catalyze the oxidation reaction of VOCs at a lower temperature, thereby reducing energy consumption and achieving the effect of energy saving and synergistic carbon reduction. By introducing Ce into the precious metal Pt active component, the activity of the catalyst is improved, and the amount of Pt is reduced. By introducing Ti into the active component, not only the catalytic reaction temperature is reduced, but also the catalytic reaction activity is improved, thereby greatly improving the application range of the catalyst, and having good application prospects.

[0086] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry. It is characterized in that The active components of the catalyst include: PtO 2 、CeO 2 and TiO 2 .

2. A low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry according to claim 1, It is characterized in that Among the active components of the catalyst, PtO 2 The weight proportion of CeO in the catalyst is 150-500 mg / kg. 2 The weight percentage of TiO in the catalyst is 2.0-3.5w%. 2 The weight percentage in the catalyst is 1.0-1.8w%.

3. A low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry according to claim 1, It is characterized in that The catalyst carrier is honeycomb ceramic.

4. A low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry according to claim 3, It is characterized in that The catalyst carrier components include: SiO 2 、Al 2 O 3 ,MgO,Fe 2 O 3 , CO 2 and ZrO 2 .

5. A low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry according to claim 4, It is characterized in that In the catalyst, the weight proportion of the carrier is 94-98%.

6. A low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry according to claim 5, It is characterized in that The catalyst carrier components include: 38-48w% SiO 2 、35-45w%Al 2 O 3 ,8-12w%MgO,0.1-0.5w%Fe 2 O 3 、0.1-0.5w%CO 2 and 0.2-0.7w% ZrO 2 .

7. A method for preparing a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry. It is characterized in that include: Obtain ceramic raw materials to prepare a carrier of the catalyst, wherein the carrier of the catalyst is a honeycomb ceramic; wherein, by mass percentage, SiO 2 The content is 38-48%, Al 2 O 3 The content is 35-45%, the MgO content is 8-12%, and the Fe 2 O 3 The content is 0.1-0.5%, CO 2 The content is 0.1-0.5%, ZrO 2 The content is 0.2-0.7%, H 2 O content is less than 2%; The honeycomb ceramic is immersed in HNO with a pH of 4-6. 3 Acid etching is performed in the solution, and after filtering out, it is neutralized with a NaOH solution with a pH of 8-9, and rinsed with deionized water for 3-5 times. After drying, active component coating is performed to obtain a finished catalyst.

8. The method for preparing a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry according to claim 7, It is characterized in that The process of coating the active component includes: S1: weigh the honeycomb ceramic; S2: Weigh a certain amount of Ce(NO 3 ) 3 6H 2 O、Pt(NO 3 ) 2 and TiF 4 The powder was placed in deionized water and stirred using a magnetic stirrer for 0.5 h until fully dissolved; S3: Place the honeycomb ceramic in the mixed solution and slowly add 5w% NH 3 ·H 2 O solution until pH = 10, then sealed and aged at room temperature for 12 hours; S4: Wash the sample alternately with anhydrous ethanol and deionized water 3 times each; S5: Dry the washed sample in an oven at 90°C for 12 h; S6: The obtained precursor was calcined in a muffle furnace at 500 °C for 3 h, with the heating rate set at 2 °C min -1 ; S7: Allow the finished catalyst calcined in the muffle furnace to cool naturally to room temperature.

9. Application of a low-temperature oxidation catalyst for VOCs in exhaust gas from the auto repair industry, which is used to remove VOCs in exhaust gas from spray paint booths.

Citation Information

Patent Citations

  • Catalytic combustion catalyst, and preparation method and application thereof

    CN106540754A

  • Furniture spray paint waste gas treatment apparatus

    CN107998820A

Cited By

  • Adsorption catalyst as well as preparation method and application thereof

    CN120438000A